Development of Ejector Cooling System for Vegetables Products Vacuum Cooling - Sulaiman; Desmi Asriandi (Jurnal Teknik Mesin, 2016)
Nowadays, the development of refrigeration technology is more rapidly, the adicted of people to refrigeration system from year to year is always rising,start from the simple scale (eg,refrigerator) in order to safe foods until the big scale such as in industry. The ejector designed will change the capillar tube function or TXV to improve the AC mechine performance. Theoritically,the use of ejector in this research will increase the effect of refrigeration and decrease compression performance. The increasing work of the system will decrease the eletrical energy consumption at the time the air conditioner work. The test in the research is designed in such a manner, so that it can be operated in standard or conventional condition (the system operates normally by using capilar tube) and in the condition of using ejector and doing cooling vacuum. Based on the test by using AC in kind of split with 2 HP Compressor capacity,it is concluded that there has been increasing of COP (Coeficient Of Performance) after using ejector in refrigeration system with vacuum cooling about 1,2 % and also there is retrenchment use of electricity about 0,01 %.